Development of a drama gong performance model: an effort to preserve the traditional Balinese drama in the digital era - I Wayan Sugita; I Gede Tilem Pastika; I Made Gde Puasa (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2023)
Drama Gong is a traditional Balinese performance art that enjoyed popularity. However, since the 1990s, the advent of television and the internet has led to a decline in the prominence of Drama Gong. Therefore, there is a pressing need to revitalize and innovate this traditional art form. One such effort by Balinese artists involves the creation of a digital adaptation known as 'Drama Keraton Cilinaya.' This qualitative descriptive research aims to explore the development model of Drama Gong in the digital era. The research data were collected through a comprehensive document analysis, which included the examination of seven episodes of 'Drama Keraton Cilinaya,' as well as direct observations and interviews with the creators. The findings revealed that 'Drama Keraton Cilinaya' has undergone significant internal and external innovations. Internally, the artists emphasized the importance of having an open mindset to embrace global changes, packaged stories for enhanced appeal and comprehension, incorporated contemporary dialogue, employed multiple languages, engaged younger talents, enhanced makeup and costume artistry, introduced digital music, and improved stage layouts. External innovations involve collaborations with artists beyond the Drama Gong tradition, utilizing digital technology in production, and distributing the performances through TV media and YouTube channels to broaden their audience reach. It is anticipated that the findings of this research will serve as a valuable digital packaging model, not only for Drama Gong but also for the development of other traditional Balinese performing arts, ensuring their sustainability in the digital era.